Thesea pyrrha sp. nov., a new shallow-water octocoral (Cnidaria, Anthozoa) from southwestern Atlantic, and implications on the systematics of the genus - Carpinelli, Ágatha Nascimento; Cordeiro, Ralf Tarciso Silva; Castro, Clovis Barreira; Kitahara, Marcelo Visentini (Zootaxa, 2022)
The family Plexauridae Gray, 1859 is characterized by grouping octocorals that have thick branches and coenenchyme. However, due to their relatively simple body plan, the establishment of homologous and, therefore, systematically informative morphological characters is a challenge for the systematics of Octocorallia. During the last decade, molecular studies suggested that Plexauridae is polyphyletic, with representatives grouping with Acanthogorgiidae Gray, 1859 and also Gorgoniidae Lamouroux, 1812. Represented by 22 extant species, mostly of which occur in the Atlantic Ocean, the plexaurid genus Thesea Duchassaing & Michelotti, 1860 has also been purported to be polyphyletic, with a Pacific lineage related to the former “Paramuriceidae” and an Atlantic lineage more closely related to Gorgoniidae. Thus, aiming to further improve our understanding of the evolutionary position of the Southwestern Atlantic Thesea, sequencing of the extended Octocorallia barcode reinforces the need for a re-evaluation of the position of the genus within plexaurids. Molecular and macro and micromorphological analyzes indicate the occurrence of an undescribed species distributed from Rio de Janeiro to Santa Catarina, here named Thesea pyrrha sp. nov. Results presented herein also suggest that T. pyrrha is close related to Adelogorgia and Psammogorgia, both genera exclusive to the Pacific Ocean.